2009
DOI: 10.1111/j.1540-6229.2009.00242.x
|View full text |Cite
|
Sign up to set email alerts
|

House Price Changes and Idiosyncratic Risk: The Impact of Property Characteristics

Abstract: To assess the quality of the fit in a multiple linear regression, the coefficient of determination or R 2 is a very simple tool, yet the most used by statistics users. It is well known that the classical (least-squares) fit and coefficient of determination can be arbitrary misleading in the presence of a single outlier. In many applied setting, the assumption of normality of the error and of absence of outliers are difficult to establish. In these cases, robust procedures for the estimation and the inference i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
23
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(29 citation statements)
references
References 44 publications
6
23
0
Order By: Relevance
“…To probe this further, we examine whether there is any significant difference in the investment performance of good construction quality homes. This line of enquiry is consistent with prior studies which found that houses do not appreciate at the same rate due to their property attributes, such as age, type and location (Smith and Tesarek, 1991;Archer et al, 1996;Smith and Ho, 1996;Clapp and Giaccotto, 1998;Coulson and Lahr, 2005;Harding et al, 2007;Bourassa et al, 2009;Ferreira and Gyourko, 2012).…”
Section: Construction Quality and House Pricessupporting
confidence: 88%
See 3 more Smart Citations
“…To probe this further, we examine whether there is any significant difference in the investment performance of good construction quality homes. This line of enquiry is consistent with prior studies which found that houses do not appreciate at the same rate due to their property attributes, such as age, type and location (Smith and Tesarek, 1991;Archer et al, 1996;Smith and Ho, 1996;Clapp and Giaccotto, 1998;Coulson and Lahr, 2005;Harding et al, 2007;Bourassa et al, 2009;Ferreira and Gyourko, 2012).…”
Section: Construction Quality and House Pricessupporting
confidence: 88%
“…Hence, it would be insightful to calibrate to what extent capital appreciation of housing is related to construction quality. This line of enquiry extends a stream of the literature which finds that price appreciation of houses is not homogenous (see Smith and Tesarek, 1991;Archer et al, 1996;Smith and Ho, 1996;Clapp and Giaccotto, 1998;Coulson and Lahr, 2005;Harding et al, 2007;Bourassa et al, 2009;Ferreira and Gyourko, 2012).…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…Notes 1. Bourassa et al (2009) show that housing price dynamics also can vary across individual units within a metropolitan area. The variation in dynamics across individual units is beyond the scope of this paper.…”
Section: Fundingmentioning
confidence: 99%